14-3-3 interaction with phosphodiesterase 8A sustains PKA signaling and downregulates the MAPK pathway - Mukherjee, Soumita (2024)
The cAMP/PKA and mitogen-activated protein kinase (MAPK) signaling cascade control many cellular processes and are highly regulated for optimal cellular responses upon external stimuli. Phosphodiesterase 8A (PDE8A) is an important regulator that inhibits signaling via cAMP-dependent PKA by hydrolyzing intracellular cAMP pool. Conversely, PDE8A activates the MAPK pathway by protecting CRAF/Raf1 kinase from PKA-mediated inhibitory phosphorylation at Ser259 residue, a binding site of scaffold protein 14-3-3. It still remains enigmatic as to how the cross-talk involving PDE8A regulation influences cAMP/PKA and MAPK signaling pathways. Here, we report that PDE8A interacts with 14-3-3ζ in both yeast and mammalian system, and this interaction is enhanced upon the activation of PKA, which phosphorylates PDE8A's Ser359 residue. Biophysical characterization of phospho-Ser359 peptide with 14-3-3ζ protein further supports their interaction. Strikingly, 14-3-3ζ reduces the catalytic activity of PDE8A, which upregulates the cAMP/PKA pathway while the MAPK pathway is downregulated. Moreover, 14-3-3ζ in complex with PDE8A and cAMP-bound regulatory subunit of PKA, RIα, delays the deactivation of PKA signaling. Our results define 14-3-3ζ as a molecular switch that operates signaling between cAMP/PKA and MAPK by associating with PDE8A.